Ocean variability drives a millennial-scale shift in South Pacific hydroclimate - Mark Peaple; Daniel T. Skinner; Gordon N. Inglis; Manoj Joshi; Peter Langdon; Adrian J. Matthews; Timothy J. Osborn; David Sear (Communications Earth & Environment)
Abstract The South Pacific Convergence Zone is a band of intense austral summer rainfall in the tropical Pacific. Changes in the South Pacific Convergence Zone are linked to Pacific sea surface temperatures on decadal timescales, but its behaviour and impacts over longer timescales remain poorly understood due to limited proxy records and model uncertainties. We combine new plant wax hydroclimate records with existing proxy evidence and climate model simulations to investigate South Pacific Convergence Zone changes over the past 1500 years. Our findings indicate that between 1000 and 200 years ago, the eastern South Pacific Convergence Zone became wetter while the western part became drier. Model simulations suggest that these centennial-scale changes were driven by Pacific sea surface temperature gradients. This eastward shift coincides with Polynesian colonisation, implying hydroclimate shifts both ‘pushed’ migration eastward and ‘pulled’ successful eastern settlement.